2020
DOI: 10.1155/2020/7860324
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin Effect on Pregnancy Outcomes in a Patient with Elevated Plasminogen Activator Inhibitor-1

Abstract: Background. Plasminogen activator inhibitor-1 (PAI-1) inhibits tPA and creates a prothrombotic state. Gene polymorphisms of PAI-1 are associated with elevated levels and adverse pregnancy outcomes. Case. A 36-year-old gravida 6, para 1-1-3-1 with elevated prepregnancy PAI-1 levels, a history of early-onset preeclampsia with severe features superimposed on chronic hypertension, intrauterine growth restriction (IUGR), and recurrent pregnancy loss (RPL), presented with a dichorionic-diamniotic twin gestation. She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…Nonetheless, subjects with the 4G allele experienced a 1.27-fold elevated risk of developing pre-eclampsia [6,79]. Similarly to our study, a meta-analysis of 18-case control studies revealed that the 4G/5G polymorphism is related to an elevated risk of pre-eclampsia, RPL, and advocated PAI-1 examination as well as anticoagulant therapy [6,77].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Nonetheless, subjects with the 4G allele experienced a 1.27-fold elevated risk of developing pre-eclampsia [6,79]. Similarly to our study, a meta-analysis of 18-case control studies revealed that the 4G/5G polymorphism is related to an elevated risk of pre-eclampsia, RPL, and advocated PAI-1 examination as well as anticoagulant therapy [6,77].…”
Section: Discussionsupporting
confidence: 74%
“…PAI-1 is characterized by anti brinolytic activity via inhabiting tissues PA, and hence opposing brinolysis besides enhancing a procoagulant state during pregnancy, attenuating bleeding, and improving the stability of clot. PAI-1 elevated levels in pre-eclampsia can lead to the onset of placental damage 77 [77].…”
Section: Discussionmentioning
confidence: 99%
“…В метаанализе, проведенном K. Giannakou в 2018 г., включающем 1466 первичных исследований, оценивающих генетические и негенетические факторы преэклампсии, гомозиготный полиморфизм PAI-1 оказался единственным генетическим полиморфизмом, имеющим достоверные доказательства вклада в развитие преэклампсии [17]. Хотя в настоящее время ряд авторов обращают внимание не столько на наличие полиморфизма в гене PAI-1, cколько на собственно уровень ингибитора 22 активатора плазминогена 1-го типа (PAI-1) и полагают, что при его повышении следует рассматривать вопрос о назначении профилактических доз низкомолекулярных гепаринов в целях профилактики преэклампсии и невынашивания беременности [18].…”
Section:  результаты и обсуждениеunclassified